KRISIS IDENTITAS DAN SPIRITUALITAS PADA KAUM MUDA: MEMBERDAYAKAN KAUM MUDA DALAM MENCARI TUJUAN HIDUP - Marchella Winda Sirang; Brek, Yohan; Ester Karosekali (PT. Giat Konseling Nusantara, 2024)
Identity crisis among youth is a complex challenge where individuals struggle to find their identity and meaning in life. This article discusses the importance of support from counselors, communities, and parents in helping adolescents face this crisis. Through a qualitative approach, this research explores the role of pastoral counselors in providing spiritual and emotional guidance, as well as effective counseling techniques such as faith-based cognitive-behavioral therapy and spiritual meditation. Furthermore, the article highlights the significance of collaboration among various parties to create a safe and supportive environment while providing the necessary resources for youth. Thus, this collective support is expected to empower young people in their search for spiritual meaning and life purpose.